Mn/carbon aerogels derived from the water-induced self-assembly of UIO-66 (Mn) for the thermal decomposition of ammonium perchlorate - Zhao, Jun; Liu, Yang; Wang, Hui; Fu, Xu cheng; Deng, Neng mei (Frontiers in Chemistry, 2024)
In solid propellants, combustion catalysts play a crucial role. Here, we introduce a convenient method for the self-assembly of UIO-66 (Mn) in the presence of water, leading to the preparation of Mn/C aerogels. The aerogels were successfully utilized in the thermocatalytic decomposition of ammonium perchlorate (AP). The results indicate that the incorporation of 2% mass fraction of Mn/C aerogels enhances the peak temperature of AP decomposition by approximately 87.5°C. Mn/C aerogels demonstrate excellent catalytic performance. In combination with kinetics, we propose a thermal catalytic mechanism.